2023
DOI: 10.3390/plants12010180
|View full text |Cite
|
Sign up to set email alerts
|

Species- and Metal-Specific Responses of the Ionome of Three Duckweed Species under Chromate and Nickel Treatments

Abstract: In this study, growth and ionomic responses of three duckweed species were analyzed, namely Lemna minor, Landoltia punctata, and Spirodela polyrhiza, were exposed for short-term periods to hexavalent chromium or nickel under laboratory conditions. It was found that different duckweed species had distinct ionomic patterns that can change considerably due to metal treatments. The results also show that, because of the stress-induced increase in leaf mass-to-area ratio, the studied species showed different order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Besides remediation, metal accumulation may also gain significance when future duckweed-based feed and food production is considered. Accordingly, Pakdee et al [ 29 ] identified metallothionein-like genes and analysed dynamics in their transcript abundances under Cu and Cd stress, while, in another study, Oláh et al [ 30 ] compared changes in the biomass ionomic composition of different duckweed species in response to acute Ni and Cr(VI) stress and the localization of heavy metal accumulation in the fronds.…”
Section: Phytoremediation: Wastewatermentioning
confidence: 99%
“…Besides remediation, metal accumulation may also gain significance when future duckweed-based feed and food production is considered. Accordingly, Pakdee et al [ 29 ] identified metallothionein-like genes and analysed dynamics in their transcript abundances under Cu and Cd stress, while, in another study, Oláh et al [ 30 ] compared changes in the biomass ionomic composition of different duckweed species in response to acute Ni and Cr(VI) stress and the localization of heavy metal accumulation in the fronds.…”
Section: Phytoremediation: Wastewatermentioning
confidence: 99%